Surface ultrastructure of excysted metacercariae of Haplorchis taichui (Trematoda: Heterophyidae) - Sukontason KL. (2014)
The morphology of newly excysted juvenile Haplorchis taichui was studied using a light and a scanning electron microscope (SEM). The reproductive organs were well developed. The whole body surface was covered with numerous transverse rows of scale-like spines, which had 3-11 points at the tip. The spines on the dorsal were similar with those on the ventral surfaces in shape, size and number of points. The spines in anterior were digitated into 10-11 points, then 8-9 points and 7 points. The presence of 3 points in each spine was observed in the area adjacent to the excretory pore. Two types of sensory papillae existed throughout the body: type I, ciliated knob-like swellings and type II, round swellings of the tegument. The rapid maturation of H. taichui results from the development of both internal and external organs during the newly excysted stage.